Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1061/(asce)mt.1943-5533.0001760
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Deformations of Geocell-Reinforced Recycled Asphalt Pavement Bases under Cyclic Loading

Abstract: A significant amount of recycled asphalt pavement (RAP) material is produced from flexible pavement rehabilitation projects. RAP can be used as a base course material for sustainable pavement construction. Performance of a pavement largely depends on the strength of its foundation, which consists of the subgrade and base course layers. Geocell was used in this study to increase the strength of RAP bases. Nine large-scale laboratory cyclic plate loading tests were conducted on unreinforced and geocell-reinforce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…At such a stage, Powell et al (1984) showed that 500 axle passages is a likely maximum. Thakur et al (2016) only applied 100 cycles of 550 kPa pressure to evaluate deformation of geocell-reinforced recycled asphalt pavement bases subjected to repetitive loading. Similarly Sun et al (2015) who applied 100 cycles of pressure at various loading increments up to 700 kPa to investigate the performance of geogrid-stabilized unpaved roads under cyclic loading.…”
Section: Test Box and Simulated Loadingmentioning
confidence: 99%
“…At such a stage, Powell et al (1984) showed that 500 axle passages is a likely maximum. Thakur et al (2016) only applied 100 cycles of 550 kPa pressure to evaluate deformation of geocell-reinforced recycled asphalt pavement bases subjected to repetitive loading. Similarly Sun et al (2015) who applied 100 cycles of pressure at various loading increments up to 700 kPa to investigate the performance of geogrid-stabilized unpaved roads under cyclic loading.…”
Section: Test Box and Simulated Loadingmentioning
confidence: 99%
“…Similarly, a threedimensional honeycomb structure called geocell offers overall confinement and higher load carrying capacity [1,[5][6][7]. However, their benefit in terms of reduced deformations and improved pavement performance over soft subgrades is observed when reinforcement is placed near the loading region [8][9][10][11]. In most cases, when soft subgrades are encountered, single reinforcement such as geogrid or geocell placement in the base layers may not be adequate to control the pavement deformations.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of these studies, it can be observed that the shear strengths increase significantly using geocell in soil samples. Moreover, many researchers have investigated the bearing capacity of footings with geocell-reinforced soil (Latha et al, 2006;Latha and Murthy, 2007;Dash et al, 2007;Sitharam et al, 2007;Wang et al, 2008;Moghaddas Tafreshi and Dawson, 2010;Yang et al, 2012;Tavakoli Mehrjardi et al, 2012;Tanyu et al, 2013;Dash and Chandra, 2013;Chen et al, 2013;Huang, 2014;Song et al, 2014;Han and Thakur, 2014;Moghaddas Tafreshi et al, 2015;Avesani Neto et al, 2015;Aboobacker et al, 2015;Biabani et al, 2016;Kumar and Saride, 2016;Sireesh et al, 2016;Hegde et al, 2016;Thakur et al, 2016;Mehrjardi et al, 2019). Last of all, through the studies performed on the bearing capacity of shallow foundations using reinforced soil with geocell, it was established that the bearing capacity of soil increases with the use of geocell.…”
Section: Introductionmentioning
confidence: 99%